FUNGSI MANAJEMEN PENGGERAKAN (ACTUATING) DALAM PERSPEKTIF AL-QUR’AN - Istiqomah (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2026)
This study aims to examine the function of management actuating from the perspective of the Qur’an and its relevance to modern management theory. This research employs a qualitative approach using a library research method by analyzing management literature, Islamic management texts, Qur’anic verses, prophetic traditions, and relevant scholarly articles. The findings indicate that the actuating function in Islamic management emphasizes ethical and spiritual dimensions such as just leadership, effective communication, intrinsic motivation, responsibility, consultation (shura), and sincerity. Core values including tawhid, amanah, justice, and consultation serve as moral foundations in the implementation of actuating functions. Therefore, management actuating in the Qur’anic perspective integrates organizational effectiveness with moral and spiritual development, particularly within Islamic educational institutions.